Examining the Second-Order Factor Structure of the Gender Minority Stress and Resilience Scale - Dolezal, Michael L. (Journal of interpersonal violence, 2023)
The gender minority stress and resilience (GMSR) theory and associated measure are widely utilized in research investigating the stress, resilience, and psychological health experiences of gender nonconforming (GNC) individuals. GMSR theory specifies that distal stress and proximal stress experiences adversely affect the psychological health of GNC individuals, while resilience factors help buffer against these deleterious impacts. Moreover, GMSR theory clearly specifies a second-order factor structure such that distal stress experiences are comprised of gender-based victimization, rejection, discrimination, and non-affirmation; proximal stress experiences are comprised of internalized transphobia, negative expectations for the future, and gender identity nondisclosure; and pride and community connectedness constitute resilience factors. However, despite widespread use of the GMSR measure, including validating its use among Italian, Spanish, and adolescent GNC individuals, all research to date has only queried the first-order factor structure of the measure. The present study therefore evaluated the second-order factor structure of the GMSR measure among a sample of 234 GNC college students. Results suggested that the second-order factor structure provided a reasonable fit to the data but did not fit the data exceptionally well. Moreover, results suggested that the first-order factor structure with correlated factors provided a better fit to the data than did the second-order model. Thus, while this study found support for the second-order factor structure, it appears that the first-order structure may be better suited for research use. Secondarily, the GMSR measure appears valid for use among GNC undergraduates. Additional research is needed to further validate the measure’s second-order factor structure, and future research should consider trimming redundant items from the GMSR to address known fit issues.